Performance-Based Management in Public Administration: Implications for Economic Growth and Service Delivery - Putri, Walla Astianty; Novitri, Bella Suci; Utami, Pri; Muhtadi, TB. Yudi; Rianto, Joko; Ahmad, Ahmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study explores the role of performance-based management (PBM) in public administration and its implications for economic growth and service delivery. Performance-based management has emerged as a strategic approach to enhance efficiency, accountability, and transparency in government institutions by linking organizational goals with measurable outcomes. Through a systematic review of relevant literature and comparative case studies from various countries, this research highlights how PBM fosters improved resource allocation, promotes evidence-based policymaking, and strengthens institutional capacity. The findings indicate that PBM contributes to economic growth by ensuring more effective public expenditure management, stimulating investment confidence, and fostering innovation in the public sector. Furthermore, PBM positively impacts service delivery by improving responsiveness, citizen satisfaction, and the quality of public services. However, challenges such as limited institutional readiness, inadequate performance measurement systems, and resistance to cultural change remain significant barriers to its full implementation. This study concludes that integrating PBM into public administration can play a pivotal role in driving sustainable economic development and enhancing governance, provided that robust monitoring mechanisms and capacity-building initiatives are prioritized.